Monoclonal antibody specific for Listeria monocytogenes associated with a 66-kilodalton cell surface antigen. - Bhunia, A K (1992)
A monoclonal antibody (MAb), EM-7G1, specific for Listeria monocytogenes was developed by using a previously developed MAb, C11E9 (A. K. Bhunia, P. H. Ball, A. T. Fuad, B. W. Kurz, J. W. Emerson, and M. G. Johnson, Infect. Immun. 59:3176-3184, 1991), to mask epitopes shared by L. monocytogenes and Listeria innocua in a 66-kDa cell surface protein. MAb EM-7G1 was an immunoglobulin subclass G1 antibody with kappa light chains. This MAb reacted with all 34 strains of L. monocytogenes tested and showed no cross-reaction with other Listeria spp. or other gram-positive or gram-negative organisms tested by enzyme-linked immunosorbent assay, dot blotting, and colony blotting. A second MAb, EM-6E11, reacted with all Listeria spp. tested but no other bacteria. In a Western blot (immunoblot) assay, EM-7G1 reacted with a crude cell surface protein of 66 kDa with a pI value of 6.7, while EM-6E11 reacted with two protein bands of 43 and 94 to 97 kDa with pI values of 4.0 and 4.3, respectively. Results with trypsin or pronase treatments indicated that the cell antigen reacting with EM-7G1 was on the surface of L. monocytogenes V7 and Scott A cells.